A New View of the Economics of International Readjustment - Balogh, Thomas (Review of Economic Studies, 1946)
Journal Article A New View of the Economics of International Readjustment Get access Thomas Balogh Thomas Balogh Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 2, 1946, Pages 82–94, https://doi.org/10.2307/2296088 Published: 01 September 1946